Pembrolizumab as a monotherapy or in combination with platinum-based chemotherapy in advanced non-small cell lung cancer with PD-L1 tumor proportion score (TPS) ≥50%: real-world data. (1st January 2021) - Dudnik, Elizabeth; Moskovitz, Mor; Rottenberg, Yakir; Lobachov, Anastasiya; Mandelboim, Rinat; Shochat, Tzippy; Urban, Damien; Wollner, Mira; Nechushtan, Hovav; Rotem, Ofer; Zer, Alona; Daher, Sameh; et al.
ABSTRACT: Both pembrolizumab (P) and combination of pembrolizumab with platinum-based chemotherapy (PCT) represent standard 1 st -line options for advanced non-small cell lung cancer (aNSCLC) with PD-L1 tumor proportion score (TPS) ≥50%. The two strategies have never been compared in a randomized trial. 256 consecutive patients with EGFR/ALK/ROS1 -wild-type PD-L1 TPS ≥50% aNSCLC receiving P (group P, n = 203) or PCT (group PCT, n = 53) as a 1 st -line treatment were identified in the electronic databases of 4 Israeli cancer centers. Time-to-treatment discontinuation (TTD) and overall survival (OS) were assessed. Baseline characteristics were well balanced, except for age and ECOG PS differences in favor of group PCT. Median (m)TTD was 4.9 months (mo) (95% CI, 3.1–7.6) vs 8.0mo (95% CI, 4.7–15.6) ( p -0.09), mOS was 12.5mo (95% CI, 9.8–16.4) vs 20.4mo (95% CI, 10.8-NR) ( p -0.08), with P and PCT, respectively. In the propensity score matching analysis (n = 106; 53 patients in each group matched for age, sex and ECOG PS), mTTD was 7.9mo (95% CI, 2.8–12.7) vs 8.0mo (95% CI, 4.7–15.6) ( p -0.41), and mOS was 13.3mo (95% CI, 6.8–20.3) vs 20.4mo (95% CI, 10.8-NR) ( p -0.18), with P and PCT, respectively. Among various subgroups of patients examined, only in females (n = 86) mOS differed significantly between treatments (10.2mo (95% CI, 6.8–17.2) with P vs NR (95% CI, 11.4-NR) with PCT; p -0.02). In the real-world setting, no statistically significant differences in long-term outcomes with P vs PCT were observed; a prospective randomized trial addressing the comparative efficacy of P and PCT in different patient subgroups is highly anticipated.List of abbreviations : AE - adverse events; ALK - anaplastic lymphoma kinase gene; ALT - alanine aminotransferase; (a)NSCLC - (advanced) non-small cell lung cancer; AST - aspartate aminotransferase; BRAF - v-Raf murine sarcoma viral oncogene homolog B; BRCA2 - BReast CAncer gene 2; c-Met - tyrosine-protein kinase Met; CTCAE, v. 4.03 - Common Terminology Criteria for Adverse Events, version 4.03; CTLA-4 - cytotoxic T-lymphocyte-associated protein 4; ECOG PS - Eastern Cooperative Oncology Group performance status; EGFR - epidermal growth factor receptor gene; FISH - fluorescent in situ hybridization; HER2 - human epidermal growth factor receptor 2; IC - tumor-infiltrating immune cells; ICI - immune check-point inhibitors; IHC - immunohistochemistry; IQR - interquartile range; irAE - immune related adverse events; ISCORT - Israeli Society for Clinical Oncology and Radiotherapy; KRAS - Kirsten rat sarcoma viral oncogene homolog; (m)TTD -(median) time-to-treatment discontinuation; mo - months; (m)OS - (median) overall survival; (m)PFS - (median) progression-free survival; muts/Mb - mutations per megabase; NA - not specified/not available; NOS - not otherwise specified; NR - not reported/not reached; ORR - objective response rate; P - pembrolizumab; PCR - polymerase chain reaction; PCT - combination of pembrolizumab with platinum-based chemotherapy; PD – progression of disease; PD-1 - programmed cell death-1; PD-L1 - programmed cell death ligand-1; pts - patients; RET - proto-oncogene RET; ROS1 - proto-oncogene tyrosine-protein kinase ROS1; SD - standard deviation; STK11 - serine/threonine kinase 11; TC - tumor cells; TMB - Tumor mutation burden; TPS - tumor proportion score.